Ø§Ø³ØªÙƒØ´Ø§Ù Ø¨Ø±Ù†Ø§Ù…Ø¬ Ø£Ø³Ø¨ÙˆØ¹ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„ØªÙˆØ§ØµÙ„ÙŠ ÙÙŠ Ù…Ø¹Ù‡Ø¯ Ø§Ù„Ø¥ØµÙ„Ø§Ø Ø¬Ù…Ø¨Ø± Ø¬Ø§ÙˆÙ‰ Ø§Ù„Ø´Ø±Ù‚ÙŠ - Rodiatul Maghfiroh; Sugirma Sugirma; Wildana Wargadinata; Nurhadi Nurhadi; Mohammad Shohibul Anwar (UIN Fatmawati Sukarno Bengkulu, 2023)
AbstractThe program arabic week is a special program implemented at Jember East Java to upgrade Arabic language skills, and this program shows that language learning focus not only on theoretical aspects but Arabic language learning is communicative learning. The aim of this research is to explore the effectiveness of communicative approach in the Arabic Week program to upgrade students' Arabic language skills. The research method is qualitative research with data collection techniques through observation, interviews and documentation. The researcher used metadata analysis. The subjects of study were students at Jember East Java The results of the research showed that the use of the communicative approach in the Arabic Week program and applications was able to upgrade students' skill in the Arabic language well. The students were able to understand Arabic and use it well. The communicative approach also enriches the learning experience of students by providing opportunities to interact with others in Arabic, and raises students' confidence and motivation to learn. Based on these results, this research recommends the use of the communicative approach in learning Arabic and this research is one of the effective strategies to upgrade Arabic language skills.Keywords:Communicative Approach, Arabic WeekÂ